Pengaruh Leverage, Asset Growth, Dan Investment Opportunity Set Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Yang Terdaftar Pada Indeks Saham Syariah Indonesia / ISSI tahun 2013 - 2017) - Hayyan (Journal of Economic, Management and Entrepreneurship, 2023)
The purpose of this study is to examine the effect of Leverage, Asset Growth and Investment Opportunity Set in Firm Value. Variable leverage measured by proxy debt to equity ratio, variable asset growth measured by proxy asset growth, variable investment opportunity set measured by proxy market book to value asset, while variable firm value measured by proxy price earning ratio. This research was conducted by retrieving secondary data from the company’s financial statements published from the Indonesian Islamic Stock Index (ISSI). Thus study uses a sample of islamic manufacturing companies listed Indonesian Islamic Stock Index the period 2013 until 2017. The method of analysis of this study uses multiple regression analysis. The method of analysis of this study uses multiple regression analysis. The result of the study showed that the effect leverage was very significant on the firm value, asset growth has no significant effect on firm value, and finally the investment opportunity set has very significant effect on firm value.